SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI (Studi Kasus : PT. PLN (Persero Distribusi Jakarta Raya Area Pondok Gede)) - Ahmad Djunaedi; A’ang Subiyakto; Elvi Fetrina (UIN Syarif Hidayatullah Jakarta, 2017)
PT PLN (Persero) Pondok Gede Area is a service area and network that serves to manage company assets such as substations, cables, etc. Since 2005 until now the company is still doing employee recruitment because in the next few years many employees will retire, this will make it difficult for managers in promoting employees because the available employees have a working age and service not too far away. Not yet integrated system between Manager, Asman, and SDM so that the presentation of data for the needs of the promotion of employees who are still considered ineffective and efficient manual. Therefore the purpose of this research is to assist managers in determining the right employees to be promoted. The method of data collection using observation, interview, and literature study, system development method using RAD by using UML tools. The programming stage is done by using the programming language framework CI, MySQL, and Dreamweaver as supporting software in system development. The result of this research is a decision support system that can assist managers in making decisions to select the appropriate employees to be promoted in a certain position by using MFEP and MPE method.